2022
DOI: 10.1111/ivb.12386
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycles of the oviparous sponges Cinachyrella apion (Spirophorida) and Tethya maza (Tethyida) in a tropical intertidal environment

Abstract: Environmental factors are constantly changing in the intertidal region. Consequently, the various benthic organisms that densely colonize this ocean area had to adapt to these constant changes. Reproductive strategy might be considered one of these adaptations. However, knowledge about this aspect of the biology of marine invertebrates is still contentious for some groups, especially with regard to sponges (Porifera). Here, we investigated the effects of different environmental factors on the timing and effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 65 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…C. apion and T. maza are oviparous and are most likely gonochoric because we could find no spermatic cysts co-occurring with oocytes in active reproductive specimens (Vasconcellos & Lanna, 2022) The gonochorism/oviparity, as well as hermaphroditism/viviparity, were strongly correlated in sponges, similarly, to that observed in cnidarians (Kerr et al, 2011;Riesgo et al, 2014). Hermaphroditism and viviparity seem to be ancestral traits in poriferans, especially within class Demospongiae, with several independent acquisitions of gonochorism and oviparity in different orders, such as Tetractinellida and Tethyida (Riesgo et al, 2014).…”
Section: Life History Adaptationsmentioning
confidence: 74%
See 4 more Smart Citations
“…C. apion and T. maza are oviparous and are most likely gonochoric because we could find no spermatic cysts co-occurring with oocytes in active reproductive specimens (Vasconcellos & Lanna, 2022) The gonochorism/oviparity, as well as hermaphroditism/viviparity, were strongly correlated in sponges, similarly, to that observed in cnidarians (Kerr et al, 2011;Riesgo et al, 2014). Hermaphroditism and viviparity seem to be ancestral traits in poriferans, especially within class Demospongiae, with several independent acquisitions of gonochorism and oviparity in different orders, such as Tetractinellida and Tethyida (Riesgo et al, 2014).…”
Section: Life History Adaptationsmentioning
confidence: 74%
“…C. apion is an oviparous species with no clear periodic oogenesis (see details in Vasconcellos & Lanna, 2022). We could not find any sign of spermatogenesis in the specimens analyzed during the study, but the presence of buds (asexual reproduction) in some specimens was usually observed (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations